2016
DOI: 10.1159/000449105
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic and Thromboembolic Complications after Hepato-Biliary-Pancreatic Surgery in Patients Receiving Antithrombotic Therapy

Abstract: Background: Perioperative management for patients receiving long-term anticoagulant (AC) and antiplatelet (AP) therapy is a great concern for surgeons. This single-center retrospective study evaluated the risks of hemorrhage and thromboembolism after hepato-biliary-pancreatic (HBP) surgery in such patients. Methods: Between 2009 and 2014, 886 patients underwent HBP surgery. Patients were categorized into the AC (n = 39), AP (n = 77), or control (n = 770) group according to the administration of antithrombotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Intra-operative bleeding and peri-operative blood transfusions were associated with higher incidence of postoperative clinically relevant pancreatic fistula and with lower overall survival 671–675 . A retrospective analysis showed that the risks of haemorrhagic and thromboembolic complications after HPB surgery were not increased in patients receiving long-term anticoagulant or antiplatelet therapy 676 . According to a retrospective study, chemical thromboprophylaxis after HPB surgery was safe because it did not increase the risk of major haemorrhage and decreased the risk of pulmonary embolism 677…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-operative bleeding and peri-operative blood transfusions were associated with higher incidence of postoperative clinically relevant pancreatic fistula and with lower overall survival 671–675 . A retrospective analysis showed that the risks of haemorrhagic and thromboembolic complications after HPB surgery were not increased in patients receiving long-term anticoagulant or antiplatelet therapy 676 . According to a retrospective study, chemical thromboprophylaxis after HPB surgery was safe because it did not increase the risk of major haemorrhage and decreased the risk of pulmonary embolism 677…”
Section: Discussionmentioning
confidence: 99%
“…[671][672][673][674][675] A retrospective analysis showed that the risks of haemorrhagic and thromboembolic complications after HPB surgery were not increased in patients receiving long-term anticoagulant or antiplatelet therapy. 676 According to a retrospective study, chemical thromboprophylaxis after HPB surgery was safe because it did not increase the risk of major haemorrhage and decreased the risk of pulmonary embolism. 677 Cell salvage Intra-operative cell salvage (ICS) can help to avoid the various pitfalls of other blood conservation management strategies, such as multiple preoperative visits for autologous blood donation or complications like intra-operative hypotension with ANH.…”
Section: Prothrombin Complex Concentratementioning
confidence: 99%
“…The included articles consisted of 9 studies concerning the management of chronically ATT-received patients[ 10 , 17 - 24 ] (Table 2 ) and 10 studies regarding chemical thromboprophylaxis for VTE (Table 3 )[ 25 - 34 ]. Among the studies on the management of chronically ATT-received patients, one was a multicenter retrospective cohort analysis[ 18 ] and another was an analysis using the propensity score matching method[ 21 ]. All 10 articles on chemical thromboprophylaxis for VTE were observational studies, including three prospective and seven retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%